The pottery from the site of Wakarida - Anne Benoist; Vincent Bernard; Cecile Verdellet (Polish Archaeology in the Mediterranean, 2020)
Excavations carried out between 2012 and 2013 atWakarida in northeastern Tigray uncovered a huge quantity ofpottery distributed across the different levels identified at thesite. The different pottery assemblages collected from the siteare presented in this contribution, proposing a periodizationof the occupation of Wakarida city into two main units: PeriodI (subdivided into successive phases IA and IB) and Period II.Pottery comparisons and 14C dating provide the grounds fordating the two assemblages.